The Influence of Hook Copywriting and Social Media Content Toward Brand Awareness, Brand Image, and Purchase Decisions in MSMEs in Sleman District - Rahayu, Desta; Utama, Lavendi Kurnia; Muqaddimah, Abadila Rakha; Ayuni, Dania; Utami, Alivia Meyrizka (Sekolah Tinggi Ilmu Manajemen YKPN Yogyakarta, 2024)
The use of digital marketing creates marketing competition among MSME players. MSME players need to apply effective marketing techniques to win competition between business actors. MSME players who master copywriting techniques and attractive social media content will make the public aware of the existence of a product or brand, resulting in purchasing decisions. The research method used by researchers is a mix method, namely an approach to analyzing problems quantitatively and qualitatively. The results of this research show that copywriting hooks have no effect on brand awareness, but copywriting hooks have a significant positive effect on brand image and purchasing decisions. Instagram social media content has a significant positive effect on brand awareness, brand image and purchasing decisions. This shows that hook copywriting and social media content on the Instagram platform have an important role in marketing activities with the aim of improving consumer decision making regarding the products being marketed.